2020
DOI: 10.1093/noajnl/vdaa061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functionally distinct and interacting cancer cell subpopulations from glioblastoma with intratumoral genetic heterogeneity

Abstract: Background Glioblastomas display a high level of intratumoral heterogeneity with regard to both genetic and histological features. Within single tumors, subclones have been shown to communicate with each other to affect overall tumor growth. The aim of this study was to broaden the understanding of interclonal communication in glioblastoma. Methods We have used the U-343 model, consisting of U-343 MG, U-343 MGa, U-343 MGa 31L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…In the common aggressive cancers, and especially in GBM, phenotypic spatial and temporal heterogeneity, in both stem and non-stem cell subsets, is a dynamic process responding to treatment interventions and driven further by hypoxia. 43–45 In addition, GBM may be considered a collection of mutually interacting, mutually supporting cellular subpopulations 46 demanding the use of a multi-drug combination to achieve prolonged treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…In the common aggressive cancers, and especially in GBM, phenotypic spatial and temporal heterogeneity, in both stem and non-stem cell subsets, is a dynamic process responding to treatment interventions and driven further by hypoxia. 43–45 In addition, GBM may be considered a collection of mutually interacting, mutually supporting cellular subpopulations 46 demanding the use of a multi-drug combination to achieve prolonged treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered to be a major hurdle for successful treatment of glioblastoma, where cells may display differential drug sensitivities, thereby posing an increased risk for developing treatment resistance and the pre-existence of resistant subpopulations, as exemplified in attempts of anti-EGFR treatment and in temozolomide resistance [ 9 11 ]. Intratumoral heterogeneity among the malignant cells may arise due to variation of lines and levels of differentiation, co-evolution of populations with different genetic or epigenetic characteristics, local microenvironmental cues or a combination of these that may evoke different phenotypes [ 12 14 ]. Frequently occurring genetic alterations in glioblastoma have been connected with different phenotypic states, and cells may also appear in intermediate hybrid states due to plasticity within single tumors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the different subtypes respond differently to therapies and have differential survival times, the discovery of multiple subtypes existing within the same tumour complicates patient diagnosis and treatment (Figure 6). [175,176] Spatially distinct Figure 5. How can electrotherapy be improved in order to better treat GBM?…”
Section: Molecular and Cellular Heterogeneitymentioning
confidence: 99%
“…Since the different subtypes respond differently to therapies and have differential survival times, the discovery of multiple subtypes existing within the same tumour complicates patient diagnosis and treatment ( Figure 6 ). [ 175 , 176 ] Spatially distinct tumour fragments showed that heterogeneity increases with time resulting in different areas of the tumour being classified into different transcriptional subtypes. Further to this, multiple biopsies taken from the same tumour were analyzed for their transcription subtype.…”
Section: Mapping Electrotherapies To Glioblastoma Characteristicsmentioning
confidence: 99%